2017
DOI: 10.1111/hdi.12538
|View full text |Cite
|
Sign up to set email alerts
|

Hypoproteinemia as a prognostic risk factor for arteriovenous fistula failure

Abstract: Introduction: Any vascular access is of limited duration with many factors which influence survival in patients on chronic hemodialysis (HD). Hypoproteinemia as a marker of chronic illness is common among chronic HD patients. Our aim was to analyze the survival of the primary arteriovenous fistula (AVFs) and the risk factors which influence their patency and to test the hypothesis that patients with normal values of serum proteins have lower risk of AVF failure compared to patients with hypoproteinemia.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 38 publications
2
15
2
Order By: Relevance
“…Despite all these differences mentioned previously and the lack of a good referral system for AVF creation, we were able to achieve a 77% good successful AVF use (maturation). Our FUHD rate (23%) is actually lower than that of other singlecenter reports (32e46%) 8,9,14 or national results (36%). 12 Our maturation time and cumulative survival are in accordance to what have been previously described elsewhere.…”
Section: Discussioncontrasting
confidence: 86%
See 4 more Smart Citations
“…Despite all these differences mentioned previously and the lack of a good referral system for AVF creation, we were able to achieve a 77% good successful AVF use (maturation). Our FUHD rate (23%) is actually lower than that of other singlecenter reports (32e46%) 8,9,14 or national results (36%). 12 Our maturation time and cumulative survival are in accordance to what have been previously described elsewhere.…”
Section: Discussioncontrasting
confidence: 86%
“…Our population is younger than that of other studies in which mean age is 55e 65 years. 9,10,12,14,16,18 We found that the presence of diabetes mellitus was not that common in our study, unusual for a 40e70% incidence. 9,11e13,16,17 Similarly, peripheral vascular disease had a lower incidence than other populations (10e20%).…”
Section: Discussioncontrasting
confidence: 47%
See 3 more Smart Citations